2018
DOI: 10.1016/j.ejpoleco.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Protestant ethic and entrepreneurship: Evidence from religious minorities in the former Holy Roman Empire

Abstract: We propose a new methodology for identifying the causal effect of Protestantism versus Catholicism on the decision to become an entrepreneur. Our quasi-experimental research design exploits religious minorities' strong attachment to religious ethics and the exogenous historical determination of religious minorities' geographical distribution in the regions of the former Holy Roman Empire in the 1500s. We analyse European Social Survey data, collected in four waves between 2002 and 2008, and find that religious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Consistent with Weber's hypothesis and their own assessment of the existing literature, they found that Protestants are significantly more likely to be entrepreneurs than Catholics. They reached the same conclusion looking at the data from the European Social Survey (Nunziata and Rocco, 2014). In a related research study, Cornelius Rietveld and Elco van Burg (2014) provided evidence that Protestant entrepreneurs are more likely to have a view that their duty is to add value to society through their work and that "their work is a calling from God.…”
Section: Entrepreneurship and "The Spirit Of Capitalism"mentioning
confidence: 61%
“…Consistent with Weber's hypothesis and their own assessment of the existing literature, they found that Protestants are significantly more likely to be entrepreneurs than Catholics. They reached the same conclusion looking at the data from the European Social Survey (Nunziata and Rocco, 2014). In a related research study, Cornelius Rietveld and Elco van Burg (2014) provided evidence that Protestant entrepreneurs are more likely to have a view that their duty is to add value to society through their work and that "their work is a calling from God.…”
Section: Entrepreneurship and "The Spirit Of Capitalism"mentioning
confidence: 61%
“…Finally, van Hoorn and Maseland (2013) by using World Value Survey data concluded that unemployment brings more dissatisfaction to Protestants, suggesting they value work stronger than other groups. Nunziata and Rocco (2016) used data from Switzerland and from the European Social Survey (Nunziata and Rocco, 2014) to investigate into the relationship between entrepreneurship and religious affiliation. They concluded Protestants were significantly more likely to be entrepreneurs than other groups.…”
Section: Educationmentioning
confidence: 99%
“…Most people's religion is acquired within the family through inter-generational transmission (Myers, 1996), so those who choose to be religious tend to inherit the religion of their parents. This explains the historical persistence of the geographical distribution of religious minorities in Europe (Nunziata & Rocco, 2018, 2016) and how the individual choice to be an atheist is likely to be endogenous when modelling economic outcomes. Therefore, if we are interested in estimating the behavioural implications of religious beliefs, we must adopt a research design that aims at eliminating the bias induced by omitting latent individual characteristics.…”
Section: Introductionmentioning
confidence: 99%